A decision-making algorithm for performing or cancelling embryo transfer in patients at high risk for ovarian hyperstimulation syndrome after triggering final oocyte maturation with hCG. Issue 3 (6th June 2020) - Lainas, GT; Lainas, TG; Sfontouris, IA; Venetis, CA; Kyprianou, MA; Petsas, GK; Tarlatzis, BC; Kolibianakis, EM
Abstract: STUDY QUESTION: Can the grade of ascites, haematocrit (Ht), white blood cell (WBC) count and maximal ovarian diameter (MOD) measured on Day 3 be used to construct a decision-making algorithm for performing or cancelling embryo transfer in patients at high risk for severe ovarian hyperstimulation syndrome (OHSS) after an hCG trigger? SUMMARY ANSWER: Using cut-offs of ascites grade>2, Ht>39.2%, WBC>12 900/mm 3 and MOD>85 mm on Day 3, a decision-making algorithm was constructed that could predict subsequent development of severe OHSS on Day 5 with an AUC of 0.93, a sensitivity of 88.5% and a specificity of 84.2% in high-risk patients triggered with hCG. WHAT IS KNOWN ALREADY: Despite the increasing popularity of GnRH agonist trigger for final oocyte maturation as a way to prevent OHSS, ≥75% of IVF cycles still involve an hCG trigger. Numerous risk factors and predictive models of OHSS have been proposed, but the measurement of these early predictors is restricted either prior to or during the controlled ovarian stimulation. In high-risk patients triggered with hCG, the identification of luteal-phase predictors assessed post-oocyte retrieval, which reflect the pathophysiological changes leading to severe early OHSS, is currently lacking. STUDY DESIGN, SIZE, DURATION: A retrospective study of 321 patients at high risk for severe OHSS following hCG triggering of final oocyte maturation. High risk for OHSS was defined as the presence of at least 19 follicles ≥11 mm on the day of triggering of final oocyte maturation. PARTICIPANTS/MATERIALS, SETTING, METHODS: The study includes IVF/ICSI patients at high risk for developing severe OHSS, who administered hCG to trigger final oocyte maturation. Ascites grade, MOD, Ht and WBC were assessed in the luteal phase starting from the day of oocyte retrieval. Outcome measures were the optimal thresholds of ascites grade, MOD, Ht and WBC measured on Day 3 post-oocyte retrieval to predict subsequent severe OHSS development on Day 5. These criteria were used to construct a decision-making algorithm for embryo transfer, based on the estimated probability of severe OHSS development on Day 5. MAIN RESULTS AND THE ROLE OF CHANCE: The optimal Day 3 cutoffs for severe OHSS prediction on Day 5 were ascites grade>2, Ht>39.2%, WBC>12 900/mm 3 and MOD>85 mm. The probability of severe OHSS with no criteria fulfilled on Day 3 is 0% (95% CI: 0–5.5); with one criterion, 0.8% (95% CI: 0.15–4.6); with two criteria, 13.3% (95% CI: 7.4–22.8); with three criteria, 37.2% (95% CI: 24.4–52.1); and with four criteria, 88.9% (95% CI, 67.2–98.1). The predictive model of severe OHSS had an AUC of 0.93 with a sensitivity of 88.5% and a specificity of 84.2%. LIMITATIONS, REASONS FOR CAUTION: This is a retrospective study, and therefore, it cannot be excluded that non-apparent sources of bias might be present. In addition, we acknowledge the lack of external validation of our model. We have created a web-based calculator (http://ohsspredict.org), for wider access and usage of our tool. By inserting the values of ascites grade, MOD, Ht and WBC of high-risk patients on Day 3 after oocyte retrieval, the clinician instantly receives the predicted probability of severe OHSS development on Day 5. WIDER IMPLICATIONS OF THE FINDINGS: The present study describes a novel decision-making algorithm for embryo transfer based on ascites, Ht, WBC and MOD measurements on Day 3. The algorithm may be useful for the management of high-risk patients triggered with hCG and for helping the clinician's decision to proceed with, or to cancel, embryo transfer. It must be emphasized that the availability of the present decision-making algorithm should in no way encourage the use of hCG trigger in patients at high risk for OHSS. In these patients, the recommended approach is the use of GnRH antagonist protocols, GnRH agonist trigger and elective embryo cryopreservation. In addition, in patients triggered with hCG, freezing all embryos and luteal-phase GnRH antagonist administration should be considered for the outpatient management of severe early OHSS and prevention of late OHSS. STUDY FUNDING/COMPETING INTEREST(S): NHMRC Early Career Fellowship (GNT1147154) to C.A.V. No conflict of interest to declare. TRIAL REGISTRATION NUMBER: N/A.